Application Method Play Show and Tell in Increase Ability communicate Oral Early Childhood 5-6 Years in Kindergarten Creation Nation Rambai 2021/2022 Academic Year - Veronika Br Sembiring; Juli Yanti Harahap (International Journal of Educational Research Excellence (IJERE), 2022)
Problem main in study this that is, application method play show and tell inside increase ability communicate oral child age early. Study this aim for knowing enhancement ability communication oral child with method playing show and tell at Karya Kindergarten Nation Rambai. Study this is Study Qualitative descriptive. Deep data collection techniques study this is observation and interview. subject study this is child aged 5-6 years with a total of 14 children. object study is ability communication oral child age early through method playing show and tell to children 5-6 years old at Karya Kindergarten Nation Rambai T. A 2021-2022. Data analyzed in a manner descriptive qualitative with interviews and observations. Research results show exists enhancement ability communication oral child increase through activity play show and tell. this proven with exists increase in average ability communication oral child through activity playing show and tell, on observation initial 45% increase to 75% on observation after he did action method play show and tell. With thereby could concluded that activity play show and tell can increase communication oral child age early in TK Karya Nation Rambai.